An Analysis of Deixis in Facing the Giants Movie - Natanael, Yosua Timotius; Satria, Robby (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Deixis is a linguistic term that is used to point based on context. Without comprehending the context, it is almost impossible to understand what the deixis refers to. In movies, deictic expressions are supported by the scenes to provide the context of the reference. Therefore, this research aims to analyze deixis, regarding its types and referential distinction in Facing the Giants movie, by using the theory of Levinson (1983) and Yule (1996). As qualitative research, the researchers used observational and non-participatory techniques to collect the data and applied descriptive qualitative analysis of data reduction, data display, conclusion, and verification. The results of the research found all types of deixis, and that the referential distinction had a big role in constructing the movie scenes. The movie settings, scenes, and plot were arranged to provide the essential context of the deictic expressions. The metaphoric title of “The Giants” is also deictically used to refer to both the literal “Richland Giants team” in the movie, and the metaphorical “Goliath” in the Bible.